(untitled) (Bangladesh Critical Care Journal, 2017)
Background: Dyslipidemia is one of the main risk factors with prognostic significance in relation to coronary heart disease. Aggressive treatment has been recommended in acute coronary syndrome (ACS). We examined pattern of dyslipidemia in ST Elevation myocardial infarction (STEMI) and Non- ST elevation myocardial infarction (NSTEMI). We also compare the lipid status in between two types of myocardial infarction (MI). Methods: This cross sectional observational study was carried out enrolling 100 subjects with ST elevation and Non ST elevation Myocardial Infarction, in the Department of Cardiology, BIRDEM General Hospital, Shahbag, Dhaka, over a period of six months from January 2012 to June 2012. Fasting lipid profile was done in next morning of admission in both type of MI. Results: Mean age and gender difference was significant between STEMI and NSTEMI. Mean Cholesterol (chol), Triglyceride (TG), high density lipoprotein (HDL) and low density lipoprotein (LDL) were not statistically significant between male and female groups. All mean cholesterol, TG, HDL, LDL were significantly high in older age group. The Mean cholesterol (220.7±28.1Vs208.4±20.9), triglyceride (182.8±34.4 Vs 147.4±28.9), HDL (35.14±5.7 Vs 41.65±3.8) and LDL (160.7±26.2 Vs148.3±16.8)were also statistically significant between STEMI and NSTEMI groups (p<0.05). Conclusion: Dyslipidemia is the dominating coronary risk factors. It could be concluded that significant differences are observed between two types of MI. Lipid status is relatively more uncontrolled in ST elevated MI and must be managed with all possible therapeutic modules to minimize further complications. Bangladesh Crit Care J September 2017; 5(2): 106-109